Understanding Reactions to Informative Process Model Interventions: Ambivalence as a Mechanism of Change - Nimrod Rosler; Ori Wiener-Blotner; Orel Heskiau Micheles; Keren Sharvit (Behavioral Sciences)
Transforming the course of protracted and bloody conflicts requires changing the behaviors and minds of society members who take part in these conflicts. While studies examining the psychology of such societies point to the barriers that conflict-supporting narratives create for changing minds and behavior, a novel psychological intervention offers a new direction to facilitate openness for attitude change based on the Information Process Model (IPM). Previous studies indicated the effectiveness of this intervention in creating an unfreezing of conflict attitudes and increasing support for peace negotiation in different conflict areas. However, since the psychological process underlying its effectiveness remains underexplored, the aim of the current research is to examine the experiences of participants exposed to IPM-based messages and the role of cognitive and emotional ambivalence in facilitating the unfreezing of conflict-supporting narrative and contemplating alternative beliefs. The first study (n = 234) examines how IPM (vs. control) videos increase engagement with and ambivalence towards conflict-supporting narratives using quantitative and qualitative analysis of written Decisional Balance responses. The second study (n = 24) delves into the expressions of cognitive and emotional ambivalence following exposure to different segments of an IPM video using semi-structured interviews, and further assesses their potential influence on facilitating contemplation with newly provided information.